One of Us? From Bad Taste to Empathy. Otherness in Contemporary Hollywood Movies - Boutang, Adrienne (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2010)
This article aims to examine the way contemporary Hollywood cinema deals with the topic and the visual representation of disability. Its goal is to highlight the way social recognition of vulnerability and the requisite sensitivity involved in dealing with vulnerable bodies, have influenced recent “gross-out” comedies. In a way that is very different from the famous drama Freaks, recent comedies take into account the fine line between normality and difference, and use disability as a comic trick to question the viewer’s automatic responses to physical difference. Thus, what at first appears to be bad taste, both on an aesthetic and on an ethical level, turns out to be a clever attempt to get past the boundaries between normality and disability, and present vulnerability as a universal condition. The use of gross-out humor, and of vulgar body genres, therefore works as a trigger, calculated to disrupt boundaries and challenge classical representations of physical otherness.